Acute pancreatitis secondary to tamoxifen-associated hypertriglyceridemia: A clinical update. (January 2023) - Goraya, Muhammad Hassan Naeem; Abbasi, Ehsan ul Haq; Amin, Muhammad Kashif; Inayat, Faisal; Ashraf, Muhammad Junaid; Qayyum, Mahrukh; Hussain, Nadeem; Nawaz, Gul; Zaman, Muhammad Adnan; Malik, Adnan
Introduction: Drug-induced pancreatitis has been increasingly recognized, but it is frequently encountered as an inconspicuous etiology. The underlying mechanisms of injury vary with different drugs. Tamoxifen is a frequently used anticancer drug that acts by selective modulation of the estrogen receptor in patients with breast cancer. Tamoxifen-induced hypertriglyceridemia is a relatively rare etiological factor for acute pancreatitis. However, acute pancreatitis secondary to this adverse effect remains an exceedingly important clinicopathologic entity. Case report: We hereby delineate a rare case of acute pancreatitis secondary to hypertriglyceridemia in a patient who was on tamoxifen treatment for the past 3 years. Her serum lipase and triglyceride levels were markedly elevated at 14, 285 IU/L and 20, 344 mg/dL, respectively. The diagnosis was considered based on the findings of a standard diagnostic workup and exclusion of alternative causes of acute pancreatitis. Management and outcome: The patient was instituted prompt treatment with intravenous insulin infusion and gemfibrozil. The clinical outcome was favorable with no complications. Tamoxifen was permanently discontinued and was replaced with letrozole. Discussion: This article illustrates that acute pancreatitis should be considered in the differential diagnoses of abdominal pain and elevated pancreatic enzymes in patients undergoing tamoxifen treatment. It also underscores the importance of pre- and post-tamoxifen lipid screening, especially in patients with a history of dyslipidemia and diabetes mellitus. It will facilitate an expedient detection of hypertriglyceridemia, potentially saving patients from associated morbidity and mortality.